Innovative Human Resource Management Strategy in the Digital Era - Rismayadi, Budi (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
In the era of rapidly developing digitalization, organizations are faced with new challenges in managing their human resources (HR). Rapidly evolving technological skills, changing work paradigms and increasingly higher expectations from workers require innovative HR management approaches. This research aims to explore the innovative strategies used by organizations in managing their human resources in the era of digitalization. The research method used is a qualitative study with descriptive methods. The research results show that the implementation of innovative strategies in developing human resources (HR) in the digital era has a significant positive impact. Through an inclusive and progressive approach, organizations are able to increase employee creativity, motivation and engagement by providing opportunities to express their ideas. Training that is appropriate to current developments has also proven effective in updating employee skills so that they remain relevant in the face of technological and industrial changes. Rewarding employees strengthens a culture of appreciation and increases employee retention, while aligning HR development with the existing budget helps in optimizing the use of resources. Recording the results of HR development evaluations allows organizations to identify successes and areas of improvement in development programs. Thus, these strategies play an important role in ensuring optimal quality HR performance and sustainable contribution to organizational success in the digital era.